Adaptable Preprocessing Units and Neural Classification for the Segmentation of EEG Signals - Doering, A.; Jäger, H.; Witte, H.; Galicki, M.; Schelenz, C.; Specht, M.; Reinhart, K.; Eiselt, M. (Methods of Information in Medicine, 1999)
In this contribution, a methodology for the simultaneous adaptation of preprocessing units (PPUs) for feature extraction and of neural classifiers that can be used for time series classification is presented. The approach is based upon an extension of the backpropagation algorithm for the correction of the preprocessing parameters. In comparison with purely neural systems, the reduced input dimensionality improves the generalization capability and reduces the numerical effort. In comparison with PPUs with fixed parameters, the success of the adaptation is less sensitive to the choice of the parameters. The efficiency of the developed method is demonstrated via the use of quadratic filters with adaptable transmission bands as preprocessing units for the segmentation of two different types of discontinuous EEG: discontinuous neonatal EEG (burst-interburst segmentation) and EEG in deep stages of sedation (burst-suppression segmentation).
Keywords: EEG Processing; Neural Networks; Classification; Intensive Care